A prosódia nos livros didáticos de língua portuguesa - Oliveira, Mírian Leite Gomes de (2012)
Work with orality in the classroom is not a recent orientation. Despite being a requirement of regulators agencies of mother tongue teaching National Curriculum Parameters (PCN) and National Textbook Program (NPDB) she still occupies a limited place, because the oral is that you learn to prepare for writing. To elaborate this study, we start from the hypothesis that oral genres are not taken as the object of teaching and learning but as activity-half. Thus, an essential element for the discursive competence, prosody, is still designed in view of grammar, which impairs job with this modality in school. The research was guided by sociointeracional approach, based on conceptions of authors like Marcuschi (2008), Mello and Cavalcante (2006), and Dolz Schneuwly (2004), Castillo (1998), Milanez (1993). Therefore, in order to know the conceptions of prosody addressed in the textbook, we choose five books of high school to see how this term is worked. To complement our research, we developed a questionnaire containing questions about the oral modality as a teaching object that were answered by teachers attend State of Pernambuco. This study was conducted based on the interpretation of data obtained from questionnaires and analysis of Portuguese language textbooks in high school. The results point to the difficulty of developing practices starting from the orality as an object and not as teaching oralization of written genres and can help teachers not only recognize the importance of oral language in the school and social life of the student but also develop a systematic work in the classroom.